Geometric Morphometrics Analysis of Chelae and Carapace of the Freshwater Prawn Macrobrachium Bate, 1868 - Simanjuntak, Rich Gemilang; Eprilurahman, Rury (Biogenesis: Jurnal Ilmiah Biologi, 2019)
The shape of chelae and carapace can be used to distinguish between species of prawn. This study aims to determine the variations in the shape of chelae and carapace in several species belonging to the genus Macrobrachium using analysis of geometric morphometric. This study uses photos of specimens that have been processed with several TPS software. Data analyzed statistically by PCA using the MorphoJ software. Clustering analysis using UPGMA method using PAST software. The results showed the carapace shape grid deformation varied at the tip of the rostrum, the tip of the ocular spine and the lower curvature of the front of the carapace, and the base spines of rostrum. Grid deformation in the shape of chelae varies at the tip of the pollex, the junction between the pollex and the manus on the inferior margin of the propodus, the upper and lower points marking the junction of the dactylus with the propodus. PCA shows the total variation of the carapace shape is 82.66% which is divided into PC1: 75.11% and PC2: 7.55%. While the total variation of the shape of chelae is 87.56% which is divided into PC1: 55.49% and PC2: 32.07%. Clustering analysis shows the grouping of populations of Macrobrachium, the first group is M. latidactylus and M. sintangense, the second group includes M. horstii and M. latimanus. M. lar is a species that shows the similarity of the shape of the carapace and chelae with the two groups. M. rosenbergii and M. pilimanus are on different lines.